Pejabat Pembuat Komitmen Memutuskan Kontrak Pengadaan Barang Jasa Pemerintah Secara Sepihak - Doni Hertanto; Murti Maharani; Andini Chairani R; Mulyadi (Lex Stricta : Jurnal Ilmu Hukum, 2024)
The procurement of goods and services by the government plays an important role as an instrument for driving the national economy, especially in efforts to improve the welfare of the community. These activities typically focus on the public sector and involve the use of state budgets. In practice, the implementation of government procurement contracts often faces various challenges that may lead to breach of contract or failure to fulfill obligations. In such circumstances, the government, through the Contracting Authority (CA), has the authority to unilaterally terminate the contract as a resolution measure.